The Formation of Sex Chromosomes in Silene latifolia and S. dioica Was Accompanied by Multiple Chromosomal Rearrangements - Bačovský, Václav; Čegan, Radim; Šimoníková, Denisa; Hřibová, Eva; Hobza, Roman (Frontiers in Plant Science, 2020)
The genus Silene includes a plethora of dioecious and gynodioecious species. Two species, Silene latifolia (white campion) and Silene dioica (red campion), are dioecious plants, having heteromorphic sex chromosomes with an XX/XY sex determination system. The X and Y chromosomes differ mainly in size, DNA content and posttranslational histone modifications. Although it is generally assumed that the sex chromosomes evolved from a single pair of autosomes, it is difficult to distinguish the ancestral pair of chromosomes in related gynodioecious and hermaphroditic plants. We designed an oligo painting probe enriched for X-linked scaffolds from currently available genomic data and used this probe on metaphase chromosomes of S. latifolia (2n=24, XY), S. dioica (2n=24, XY), and two gynodioecious species, S. vulgaris (2n=24) and S. maritima (2n=24). The X chromosome-specific oligo probe produces a signal specifically on the X and Y chromosomes in S. latifolia and S. dioica, mainly in the subtelomeric regions. Surprisingly, in S. vulgaris and S. maritima, the probe hybridised to three pairs of autosomes labelling their p-arms. This distribution suggests that sex chromosome evolution was accompanied by extensive chromosomal rearrangements in studied dioecious plants.